First report of genus Cosmocercella, Steiner, 1924 (Nematoda: Cosmocercidae) in Amphibians from Argentina - Gonzalez, Cynthya Elizabeth (2012)
This is the first record of the cosmocercid nematode, Cosmocercella minor, in Argentina in the host Phyllomedusa hypochondrialis, the orange-legged Leaf Frog. The species was observed using light and scanning electron microscopy (SEM) and relevant features are described, including in males the presence of subventral adanal alae and absence of postanal caudal alae, fine structure of the vesiculated rosettes, and structure of proximal end of spicules; and in females confirmation of their amphidelphic condition.